Elderly Congregation Assistance: The Use of the YouVersion Bible Application for Personal and Digital Faith Communities - Proboyekti, Umi; Hadiwitanto, Handi; Widiningsih, Devina; Susanto, Budi (Journal of Innovation and Community Engagement, 2025)
The YouVersion Bible is a free Bible app from Life Church. YouVersion provides a digital Bible integrated with support services for reading the Bible. YouVersion provides a friend facility so users can share and read the Bible together. The completeness of these facilities provides opportunities for elderly congregations to use them personally or with the community. However, the completeness of the facilities is a challenge for elderly congregations to use them technically and to use the content for spiritual needs. The community service team consisting of a combination of personnel from the Faculty of Information Technology and the Faculty of Theology has carried out the task of organizing training and mentoring. Participants were 22 active elderly congregations familiar with technology, taking part in technical training on the use of facilities, simple Bible teaching, and the concept of a complete spiritual digital community with features that support community activities. During mentoring, participants were given independent tasks to explore the application’s features. Intensive discussions including question and answer sessions had been held both directly and via WhatsApp groups. Monitoring of application usage based on feature usage activities and badge acquisition: participants who continuously use the YouVersion Bible application features after the training is completed are 53% of the 22 participants. Digital spiritual communities have not yet been formed based on community support features. In addition, participants have not yet related the use of Bible applications, including social media, that support relationships with others online with church activities and spirituality.